2014
DOI: 10.1111/birt.12096
|View full text |Cite
|
Sign up to set email alerts
|

Shortcomings of Maternity Care in Serbia

Abstract: Actions should be taken to improve bedside manners of medical staff. In addition, the government should consider the involvement of private practitioners paid by the national insurance fund to create competition and decrease the need for informal payments and "connections."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(55 citation statements)
references
References 18 publications
1
50
0
3
Order By: Relevance
“…The same inclusion and relevance criteria were applied. Two articles (Arsenijevic et al, 2014;Stepurko et al, 2013) coauthored by researchers in the team, were indicated as 'golden hits' prior to the review.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The same inclusion and relevance criteria were applied. Two articles (Arsenijevic et al, 2014;Stepurko et al, 2013) coauthored by researchers in the team, were indicated as 'golden hits' prior to the review.…”
Section: Methodsmentioning
confidence: 99%
“…Only two qualitative studies were found to be of high quality (Arsenijevic et al, 2014;Janevic et al, 2011), while the rest was mostly of a medium level of quality. Four qualitative studies scored poorly on the checklist due to insufficient information (Straus et al, 2013;Homan et al, 2010;Parkhurst et al, 2005a, b).…”
Section: General Description Of the Selected Articles And Quality Assmentioning
confidence: 99%
See 3 more Smart Citations